THE SPATIO-TEMPORAL VARIABILITY OF MAXIMUM FLOW IN THE UZ HYDROGRAPHICAL BASIN - I.D. MIFTODE; GH. ROMANESCUAle xandru Ioan Cuza University of Iasi, Faculty of Geography and Geology, Department of Geography, Bd. Carol I 2 (Aerul şi Apa: Componente ale Mediului, 2016)
The analysis of the maximum flow, resulting from the influences of several miscellaneous control factors, leads to the empirical knowledge of the quantitative and qualitative hydrological characteristics of the rivers. The temporal and spatial variability of the maximum flow has been analyzed in this paper, based on the study of the monthly and annual maximum discharges recorded between 1985-2006, at the Valea Uzului, Cremenea, and Darmanesti hydrometric stations, in the Uz watershed. The data is provided by the Water Basin Administration Siret from Bacău which for this study was statistically processed. For the assessment of the maximum flows with different exceeding probabilities, the Pearson III empirical and theoretical curves have been utilized. The concluding results have been obtained using hydrologic regionalization relations; these take into account the specific maximum flows (qmaxp%) with different insurances, the average altitude (Hm) and the area (F) of the drainage basin (Hm/√F). By selecting maximum flows with values exceeding the flooding stage (FS), the occurrence frequency has been established in the studied area. The highest floods in the Uz hydrographical basin have occurred in the months of June-July.